c-FLIP is involved in erythropoietin-mediated protection of erythroid-differentiated cells from TNF-α-induced apoptosis - Vittori, Daniela Cecilia (2010)
The TNF-α (tumour necrosis factor) affects a wide range of biological activities, such as cell proliferation and apoptosis. Cell life or death responses to this cytokine might depend on cell conditions. This study focused on the modulation of factors that would affect the sensitivity of erythroid-differentiated cells to TNF-α. Hemin-differentiated K562 cells showed higher sensitivity to TNF-induced apoptosis than undifferentiated cells. At the same time, hemin-induced erythroid differentiation reduced c-FLIP (cellular FLICE-inhibitory protein) expression. However, this negative effect was prevented by prior treatment with Epo (erythropoietin), which allowed the cell line to maintain c-FLIP levels. On the other hand, erythroiddifferentiated UT-7 cells - dependent on Epo for survival - showed resistance to TNF-α pro-apoptotic action. Only after the inhibition of PI3K (phosphatidylinositol-3 kinase)-mediated pathways, which was accompanied by negative c-FLIP modulation and increased erythroid differentiation, were UT-7 cells sensitive to TNF-α-triggered apoptosis. In summary, erythroid differentiation might deregulate the balance between growth promotion and death signals induced by TNF-α, depending on cell type and environmental conditions. The role of c-FLIP seemed to be critical in the protection of erythroiddifferentiated cells from apoptosis or in the determination of their sensitivity to TNF-mediated programmed cell death. Epo, which for the first time was found to be involved in the prevention of c-FLIP down-regulation, proved to have an antiapoptotic effect against the pro-inflammatory factor. The identification of signals related to cell life/death switching would have significant implications in the control of proliferative diseases and would contribute to the understanding of mechanisms underlying the anaemia associated with inflammatory processes. © The Author(s) Journal compilation © 2010 Portland Press Limited.